Infrared Spectroscopic Study of Vibrational Modes in Methylammonium Lead Halide Perovskites - Glaser, Tobias; Sendner, Michael; Kowalsky, Wolfgang; Pucci, Annemarie; Lovrinčić, Robert (The journal of physical chemistry letters, 2015)
The organic cation and its interplay with the inorganic lattice underlie the exceptional optoelectronic properties of organo-metallic halide perovskites. Herein we report high-quality infrared spectroscopic measurements of methylammonium lead halide perovskite (CH3NH3Pb(I/Br/Cl)3) films and single crystals at room temperature, from which the dielectric function in the investigated spectral range is derived. Comparison with electronic structure calculations in vacuum of the free methylammonium cation allows for a detailed peak assignment. We analyze the shifts of the vibrational peak positions between the different halides and infer the extent of interaction between organic moiety and the surrounding inorganic cage. The positions of the NH3+ stretching vibrations point to significant hydrogen bonding between the methylammonium and the halides for all three perovskites.
Gesehen am 01.07.2020